Investigation of Functional Difference between TecIII and TecIV in Mammals Cos-1 Cells Using GFP Fusion Proteins - Ines Atmosukarto; Grant W. Booker (ANNALES BOGORIENSES, 2005)
Signal transduction cascades are critical components of intra- and inter-cellular communication. Key component of such cascades includes tyrosine kinases. One such family of tyrosine kinases is the Tec family of tyrosine kinases . The family of tyrosine kinases is expressed mainly in cells of the hematopoietic lineage, and mutations in at least one of its one member of this family, Btk, has so far been asociated with the human immunodeficiency disorder X-Linked Agammaglobulinemia. Two major isoforms of the Tee transcript, referred to as TecIII and TecIV has been detected in various mouse embryonic and adult tissues, as well as in a number of different hematopoietic cell lines: Tec IV is the full length Tec protein with functional PH, TH, SH3 , SH2 and Kinase domains, while TecIII is generated by the splicing out of exon 8 sequences to yield a shorter peptide with a non-functional SH3 domain. Using GFP-TecIII fusion proteins, this shorter isoform ofTec was shown to have biological characteristics that differed from TECIV.